Innovative Design of External Airbag System for Improved Automotive Safety - A. Elaidy; R. Rayner; C. Kalyvas (IEEE Open Journal of Vehicular Technology)
Pedestrians are exceptionally vulnerable in road accidents, and despite the advancements in airbag technology for vehicle occupants, fatal injuries still occur due to contact between pedestrians and vehicle components. To address this issue, an innovative solution is introduced in this research: an external airbag system designed to safeguard pedestrians in cases of brake failure. The proposed system includes four airbag modules strategically positioned within the front bumper of the vehicle. These modules are specifically designed to deploy during a collision, providing protection for the pedestrian's head, legs, and body. Equipped with a highly sensitive sensor, the system triggers the airbag electronic controller unit (ECU) upon collision detection. The external airbag curtains deploy, shielding the pedestrian's head from striking the bonnet, while an additional airbag safeguards the pedestrian's legs from impact with the front bumper. With the introduction of this innovative external airbag system, the main goal is to significantly improve road safety for all individuals and prevent numerous fatalities. The introduction of the innovative external airbag system marks a significant advancement in pedestrian safety within the realm of road accidents. By strategically positioning four airbag modules within the vehicle's front bumper and equipping them with a highly sensitive sensor, this system effectively deploys during collisions to protect pedestrians' heads, legs, and bodies. The deployment of external airbag curtains shields pedestrians' heads from striking the bonnet, while an additional airbag safeguards their legs from impact with the front bumper. Through this research and implementation, the primary objective is to enhance road safety for all individuals and mitigate the occurrence of numerous fatalities resulting from pedestrian-vehicle collisions.